Biometric analysis of protein and oil contents of soybean genotypes in different environments - Rodrigues, Josiane Isabela da Silva; Arruda, Klever Márcio Antunes; Cruz, Cosme Damião; Piovesan, Newton Deniz; Barros, Everaldo Gonçalves de; Moreira, Maurilio Alves (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to identify by biometric analyses the most stable soybean parents, with higher oil or protein contents, cultivated at different seasons and locations of the state of Minas Gerais, Brazil. Forty‑nine genotypes were evaluated in the municipalities of Viçosa, Visconde do Rio Branco, and São Gotardo, in the state of Minas Gerais, from 2009 to 2011. Protein and oil contents were analyzed by infrared spectrometry using a FT‑NIR analyzer. The effects of genotype, environment, and genotype x environment interaction were significant. The BARC‑8 soybean genotype is the best parent to increase protein contents in the progenies, followed by BR 8014887 and CS 3032PTA276‑3‑4. Selection for high oil content is more efficient when the crossings involve the Suprema, CD 01RR8384, and A7002 genotypes, which show high mean phenotypic values, wide adaptability, and greater stability to environmental variation.